Exploring the Role of Guilt in Eating Disorders: A Pilot Study - Raffone, Fabiola; Atripaldi, Danilo; Barone, Eugenia; Marone, Luigi; Carfagno, Marco; Mancini, Francesco; Saliani, Angelo Maria; Martiadis, Vassilis (Clinics and practice, 2025)
Background/Objectives: Eating disorders (EDs) are complex psychopathological conditions involving dysfunctional eating behaviors, excessive body image concerns, and impaired emotional regulation. Among moral emotions, guilt plays a significant role in ED dynamics, influencing both symptomatology and interpersonal relationships. This study examines specific guilt subtypes (normative and altruistic guilt) using a specific psychometric tool. Methods: Forty-three adults with anorexia nervosa (AN), bulimia nervosa (BN), or binge eating disorder (BED) were recruited from the Eating Disorder Center of the University of Campania “Luigi Vanvitelli” or referred by psychotherapists. Diagnoses followed DSM-5 criteria. Participants completed the Moral Orientation Guilt Scale (MOGS), assessing guilt subtypes, and the Eating Disorder Inventory-2 (EDI-2), measuring ED symptomatology. Spearman’s rank correlation and stepwise multiple regression analyses were used to identify relationships between guilt dimensions and ED-related symptoms. Results: MOGS subscales were positively correlated with ED symptomatology. Normative guilt was significantly associated with binging and purging (ρ = 0.26, p < 0.05), while altruistic guilt predicted higher interpersonal distrust (t = 3.4, p < 0.01). Regression analysis revealed that age negatively influenced interpersonal distrust (t = −2.9, p < 0.01). Conclusions: In the population examined, guilt significantly influences ED symptomatology and interpersonal functioning, with specific dimensions linked to distinct behaviors and traits. Therapeutic interventions targeting guilt may enhance treatment outcomes by addressing ED emotional underpinnings. However, the results should be interpreted with caution due to the small sample size and lack of longitudinal data to establish causality. Further research with larger samples and longitudinal designs is necessary to validate these findings.